Entrepreneurial Activity in the Context of Violent Conflict: Business and Organized Violence in Colombia1 (2011)
The Colombian private sector has been accused of promoting or profiting from violence in the country. However, the private sector's role in the violent conflict and the impact of conflict on economic and entrepreneurial activity vary, as reflected by differences in political activism in peacebuilding strategies and in costs endured according to company size, sector, and region of operations. At the same time, accounts of regional variation in conflict intensity suggest that an understanding of the Colombian context of violent conflict requires a subnational approach. This paper explores whether and how differences in regional violent conflict can be attributed to the make-up of economic organizations and entrepreneurial activity associated with the production of five natural resources (oil, coffee, bananas, emeralds, and flowers) in several Colombian regions. It is found that company-specific traits, institutions of production, and the nature of international markets have a significant impact on the link between entrepreneurial activity and regional and local dynamics of the violent conflict in Colombia. © 2011, Copyright CCSBE/CCPME.